Properties of the bivariate confluent hypergeometric function kind 1 distribution (2011)
ABSTRACT: The bivariate confluent hypergeometric function kind 1 distribution is defined by the probability density function proportional to x1ν1 − 1 x2ν2 − 11F1(α; β; −x1 − x2). In this article, we study several properties of this distribution and derive density functions of X1/X2, X1/(X1 + X2), X1 + X2 and 2 √(X1 X2). The density function of 2 √(X1 X2) is represented in terms of modified Bessel function of the second kind. We also show that for ν1 − ν2 = 1/2, 2 √(X1 X2) follows a confluent hypergeometric function kind 1 distribution.